Sustainability and Business: Can the Two Coexist? A Triple Bottom Line Approach - Khattak, Q (2011)
The focus of this research is in the area of corporate social responsibility (CSR), most notably, the link between international business and sustainability. A study of this nature is essential considering the growing importance of CSR and sustainability in today‘s global business environment. Elkington‘s triple bottom line (TBL) theory is used to categorise sustainability into three variables; economic, environmental and social considerations. The TBL is focused upon for much of this dissertation. Moreover, the research approach adopted in this dissertation is split into two sections. The first section comprises of global sustainability surveys and in depth interviews conducted by global management/strategy consultancies including Boston Consulting Group and MIT; Deloitte; Grant Thornton International; and McKinsey & Company. The second section encompasses three case studies of BP, HMV Group and IKEA. The findings from this research provide evidence that sustainability is addressed by an overwhelming majority of respondents. However, not many go beyond addressing the vague definitions of sustainability presented by the TBL and Brundtland Report of 1987. This dissertation, therefore, proposes a quadruple bottom line (QBL) which is a two tier model which incorporates a fourth variable termed applicability, which helps to mitigate, not perpetuate, the aforementioned problems. Overall, this dissertation suggests that an adoption of the QBL will help to ensure the successful appliance of sustainability initiatives with the aim of increasing competitiveness and profitability for an international business. Yet, in order to assess the extent of this new theory further empirical research will need to be conducted.